Expression of pro- and anti-inflammatory cytokines and chemokines during the ovulatory cycle and effects of aging on their expression in the uterine mucosa of laying hens. (November 2018) - Elhamouly, M.; Nii, T.; Isobe, N.; Yoshimura, Y.
Abstract: The aim of this study was to examine whether cytokines and chemokines expressed in the uterine mucosa play a role in the process of eggshell formation in the chicken uterus. Changes in the expression levels of pro- and anti-inflammatory cytokines and chemokines in the uterine mucosa during an ovulatory cycle (experiment 1) and effects of aging on their expression (experiment 2) were examined. In experiment 1, the expression of the pro-inflammatory cytokines IL1β, IL6, TNFSF15, and IFNγ, and a chemokine CX3CL1 was found to increase during eggshell biomineralization (16 h following oviposition), while anti-inflammatory TGFβ2 expression was found to increase at 4 h following oviposition. In experiment 2, a higher expression of the anti-inflammatory cytokines TGFβ2 and TGFβ3, and chemokines CXCLi2 and CX3CL1, was observed in aged hens than in young hens. A significantly higher number of macrophages and CD8+ T cells were observed in the uterine tissue of aged hens than in young hens. Furthermore, the expression of adhesion molecules associated with leukocytic infiltration was found to be higher in aged hens than in young hens. We conclude that the eggshell formation process may be affected by the pro- and anti-inflammatory cytokines and chemokines. The balanced expressions of these molecules might be disrupted in aged hens.